Relationships between Cadmium, Zinc, Cd-Peptide, and Organic Acid in Tobacco Suspension Cells - Krotz, Rachel M. (1989)
Responses of tobacco (Nicotiana tabacum) suspension cells to Cd and Zn were studied in the presence and absence of ligand of Cd-peptide in order to understand the role of this peptide versus other mechanisms in Cd and Zn accumulation and accommodation in plants. With 45 micromolar Cd and 300 micromolar Zn (non-growth-inhibiting levels), metals appeared rapidly within cells, and intracellular Cd and Zn reached medium concentrations after 6 to 10 hours. Cd-peptide was observed in response to Cd after 2 hours, but this form only accounted for ∼30% of soluble Cd after 24 hours. Peptide was not observed in cells exposed to 300 micromolar Zn for up to 7 days. Organic acid-to-metal stoichiometry indicated that endogenous organic acid content of cells was more than sufficient to complex absorbed metals and no evidence was found for stimulation of organic acid biosynthesis by Cd or Zn. Metal-complexing potential of organic acids for Cd and Zn versus endogenous cations is discussed as is vacuolar-extravacuolar distribution of metals. The absence of Cd-peptide does not limit Cd-accumulation in the system studied. Results suggest that tobacco suspension cells accommodate the presence of non-growth-inhibiting and growth-inhibiting levels of Cd and Zn by sequestration in the vacuole as complexes with endogenous organic acids and that this may be a principal means for accommodation of Cd as well as Zn in the presence and absence of Cd-peptide.